Asuhan Keperawatan Pada An. G Dengan Kejang Demam Di Ruang Anggrek 1 RSUD dr. Soeselo Kabupaten Tegal - Annisa Nikmatul Hasanah; Esti Nur Janah (STIKES Columbia Asia Medan, 2026)
Introduction: Febrile seizures are seizure episodes that occur due to an increase in body temperature above 38°C without evidence of central nervous system infection such as meningitis or encephalitis. In Indonesia, the prevalence of febrile seizures is approximately 2–5% among children aged 6 months to 3 years, and around 30% of these cases experience recurrence or recurrent febrile seizures. Therefore, an appropriate nursing care plan is required to manage patients with febrile seizures. Methods: This scientific paper employed a descriptive narrative method to illustrate the provision of nursing care to patients through the nursing process approach. The general objective of this study was to understand and implement nursing care for patients with febrile seizures. Results: The nursing diagnoses identified in patients with febrile seizures were hyperthermia, risk for injury, and knowledge deficit. Nursing interventions included hyperthermia management, safety management, and health education. Conclusion: After two days of nursing implementation, two nursing diagnoses were resolved and one was partially resolved. Discharge planning included monitoring the patient's condition, particularly for seizure signs, maintaining a safe environment, educating the family about injury prevention during seizures, and encouraging family members to continuously supervise the patient.